Frost ring distribution in Araucaria araucana trees from the xeric forests of Patagonia, Argentina - Hadad, Martín Ariel; Amoroso, Mariano Martín; Roig Juñent, Fidel Alejandro (Bosque (Valdivia), 2017)
Frost rings are defined as anatomically abnormal and ecophysiologically pathological structures. We studied frost injuries in tree-rings of Araucaria araucana trees growing at the northern limit of its natural distribution. We recorded 121 frost injuries at two sites in the northern xeric distribution of A. Araucana forests. Frost rings at both sites were primarily restricted to the middle frost ring section of the rings. These results represent the first attempt to report and describe the occurrence of these events for this species and region. These proxy records represent important indicators of extreme temperature conditions.